E-TEXTBOOKS FOR THE NEW UKRAINIAN SCHOOL: IMPLEMENTATION EXPERIENCE AND PROPOSALS - Liubomyra Iliichuk (Borys Grinchenko Kyiv Metropolitan University, 2020)
The problem of using e-textbooks in educational institutions is becoming especially relevant today, due to the rapid pace of digitalization of education. The article analyses the current legislation on the introduction of e-textbooks in the educational process of modern schools, identifies requirements for their content, structural components and capabilities. Proposals of electronic teaching aids for general secondary education institutions have been analysed. It has been noted that the active development of the market of electronic publications is due to educational needs and the reform of the New Ukrainian School. An analysis of e-textbooks for primary school, recommended by the Ministry of Education and Science of Ukraine for use in educational institutions within the All-Ukrainian experiment «Electronic textbook for general secondary education», has been conducted, their compliance with national standards has been determined taking into account the requirements set out in «The Regulations on electronic textbooks». It has been found out that the state educational policy in Ukraine contributes to the digital transformation of education, determines the priorities of electronic educational resources, and outlines the mechanisms of transition from static scanned versions of paper textbooks to interactive multimedia tools that would meet modern challenges and tasks of providing qualitative educational service. The emphasis is placed on the need to take into account and borrow the best international experience in creating and implementing electronic textbooks in educational institutions, which is dictated by the need to form a competitive and competent person capable of responding quickly to today's challenges of informatization of all spheres of public life.